TAJUK MODERASI BERAGAMA GURU PENDIDIKAN AGAMA ISLAM SMA DAN SMK DI KABUPATEN SIJUNJUNG - Asraf Kurnia; Udin Supriadi; Munawar Rahmat; Siti Aisyah; Muslim Muslim; Heri Effendi (Institut Pendidikan Tapanuli Selatan, 2024)
Islamic Religious Education Teachers are a fundamental factor that should be imbued with tolerance in the right manner. Therefore, the value of religious moderation needs to be internalized within Islamic Religious Education (PAI) teachers. This research aims to determine the religious moderation of PAI teachers in high schools (SMA) and vocational schools (SMK) in Sijunjung District. The research method used is descriptive quantitative, with data collection through questionnaires. The aspects examined include: religious moderation of PAI teachers towards minority Islamic sects, religious moderation of PAI teachers towards non-Muslims, and religious moderation of PAI teachers towards local culture (Minangkabau Natural Culture). The research population consists of PAI teachers in SMA and SMK in Sijunjung District, with a sample size of 22 individuals. The research was conducted in August 2023 and indicates that the majority of respondents tend to be moderate. Dominantly moderate responses were obtained regarding religious moderation of PAI teachers towards the local Minangkabau Natural Culture. In contrast, dominant intolerant responses were obtained regarding religious moderation of PAI teachers towards minority Islamic sects and other religions. They view Sunni Muslims as the correct form of Islam, while minority Muslims such as Shia and Ahmadiyya are considered deviant. They also hold the belief that only Muslims can be considered believers, while those of other faiths are considered non-believers, despite the fact that paradise and hell are ultimately determined by Allah's prerogative. They also oppose retail businesses and outsiders, such as people from different ethnic backgrounds, opening businesses in the Minangkabau region.